Probing the parameters of the intergalactic medium using quasars. Issue 1 (24th March 2022) - Dalton, Tony; Morris, Simon L; Fumagalli, Michele; Gatuzz, Efrain
ABSTRACT: We continue our series of papers on intergalactic medium (IGM) tracers using quasi-stellar objects (QSOs), having examined gamma-ray bursts (GRBs) and blazars in earlier studies. We have estimated the IGM properties of hydrogen column density ($N\small {\rm HXIGM}$ ), temperature, and metallicity using XMM–Newton QSO spectra over a large redshift range, with a collisional ionization equilibrium model for the ionized plasma. The $N\small {\rm HXIGM}$ parameter results were robust with respect to intrinsic power laws, spectral counts, reflection hump, and soft excess features. There is scope for a luminosity bias given both luminosity and $N\small {\rm HXIGM}$ scale with redshift, but we find this unlikely given the consistent IGM parameter results across the other tracer types reviewed. The impact of intervening high-column density absorbers was found to be minimal. The $N\small {\rm HXIGM}$ from the QSO sample scales as (1 + z ) 1.5 ± 0.2 . The mean hydrogen density at z = 0 is n 0 = (2.8 ± 0.3) × 10 −7 cm −3, the mean IGM temperature over the full redshift range is log( T /K) =6.5 ± 0.1, and the mean metallicity is [ X /H] = −1.3 ± 0.1( Z ∼ 0.05). Aggregating with our previous GRB and blazar tracers, we conclude that we have provided evidence of the IGM contributing substantially and consistently to the total X-ray absorption seen in the spectra. These results are based on the necessarily simplistic slab model used for the IGM, due to the inability of current X-ray data to constrain the IGM redshift distribution.